The Influence Of Youtube Influencer (Youtuber) On A Brand Promoted Through Social Media (Youtube) - Sintha Maulinda; Setyo Riyanto (Universitas Islam Kadiri, 2022)
An influencer is someone who has large followers on his social media accounts. With the large of followers he has, that person can give a strong and significant influence on his followers. Influencers themselves will usually influence and foster the desire of other people to shop and buy products/services that they promote on their social media accounts. Currently, influencers are widely used as a marketing strategy or commonly known as influencer marketing. The results obtained through influencer marketing are proven to be more effective and efficient; this happens because the influencers themselves can strongly believe that the product or service the product/service being promoted has guaranteed quality so that their followers are attracted to buy. Currently, the Youtube media platform has many users. It is very popular with the public, especially millennials, to enjoy a variety of exciting video content so that Youtube is used to market products and services. The purpose of this paper is to find out how significant the influence of Youtube influencers (Youtuber) is on brands that are promoted through social media (Youtube).